Response of a pipeline to ground movements caused by trenching in compressible alluvium - 372951 Carder, D. R.; Taylor, M. E.; Pocock, R. G.; Transport and Road Research Laboratory (Great Britain) (Crowthorne, Eng. : Transport and Road Research Laboratory, 1982)
08